Manipulation of rumen fermentation by bioindustrial products of cashew nut shell (Anacardiumoccidentale) to reduce methane and enhance other products - Andi Saenab; Wiryawan KG; Retnani Y; Elizabeth Wina (Indonesian Center for Animal Research and Development (ICARD), 2018)
One of the strategies to reduce methane produced by ruminants is by the application of feed additive from plant materials. One of the potential plants is cashew plant especially its shell. The cashew nut shell can be processed to become 3 bioindustrial products; ie biofat, biochar, biosmoke. The aim of this research was to evaluate the effectivity of different levels of biofat, biochar and biosmoke against methane and other fermented products.This experiment was arranged in block randomised design. The treatments were: Control (substrate=S), Biofat: S+0.25 µLmL-1, S+0.5 µLmL-1, S+0.75 µLmL-1; Biochar: S+0.1 mgmL-1, S+0.2 mgmL-1, S+0.3 mgmL-1; Biosmoke: S + 2.5 µLmL-1, S+5.0 µLmL-1, S + level7.5 µLmL-1. Each treatment was done in duplicates and the in vitro experiment was repeated 4 times. The measured variables were: total gas production, methane production, (dry matter, organic matter, NDF) degradability, ammonia concentration (NH3) and partial VFA concentration. The results showed that biofat, biochar and biosmoke reduced methane productionas much as 43.88%, 24.21%, 37.88% at the highest level of inclusion, respectively. NH3 slightly increased by biochar and biosmoke addition compared to control. Molar proportion of acetic acid decreased and propionic acid increased by addition of cashew nut shell bioindustrial products compared to control. Organik matter degradability decreased significantly with biofat and biosmoke addition. Different mechanisms of biofat, biochar and biosmoke were proposed in affecting rumen fermentation. It can be concluded that each bioindustrial product of cashew nut shell (biofat, biochar and biosmoke) can be utilised as feed additive to reduce methane and increase propionic acid in the rumen fermentation.